Building Academic Integrity: The Influence of Self-Efficacy, Ethical Environment, and Machiavellian Traits on Whistleblowing Intention of Accounting Students in Greater Jakarta - Puspita, Reni Suwandi Ade (STIE Tri Bhakti, 2025)
This study aims to examine the influence of ethical environment, Machiavellianism, self-efficacy, and whistleblowing intention in the context of academic fraud among accounting students in Greater Jakarta (Jabodetabek). The method used a quantitative approach, with questionnaires distributed to 471 respondents selected using the Roscoe sampling method. The theory used is the Theory of Planned Behavior. Data analysis was conducted using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results showed that all variables of self-efficacy, Machiavellianism, and ethical environment positively influenced whistleblowing intention. These findings suggest that high self-efficacy and a strong ethical environment can encourage them to report academic fraud. This study contributes to the development of ethical policies and practices in educational institutions.